Characterization of fine and ultrafine particles in air near a steel making plant: an Italian case. Issue 4 (13th June 2016) - Rada, Elena C.; Lodi, Marco; Teoldi, Federico; Ragazzi, Marco; Rossi, Barbara
Abstract : Purpose: – The purpose of this paper is to contribute to the qualitative and quantitative knowledge on ultrafine particles in air near a steel making plant located in an Italian site. Design/methodology/approach: – A combination of experimental methodologies was used for the online and offline monitoring and chemical characterization of particulate matter (PM) in the air near the plant. Two unfiltered twin-sampling systems were adopted, working when the plant was on/off. All condensed air samples were submitted to Ion Chromatography analysis. The same samples were submitted to acid digestion before Graphite Furnace Atomic Absorption Spectroscopy Analysis. Continuous daily PM10 samples were collected to characterize ambient air. PM10 samples were also analysed to estimate metals content. The PM size distribution was achieved by continuous online monitoring. The adopted ultrafine particulate monitor classifies particles in the range 20-200 nm. The overall size distribution was inferred from an Optical Particulate Counter able to classify particles in the range 0.3-10 µ m. Findings: – The obtained results show that no causal relationship can be found between the measurements of anions and metal in the air near the plant under investigation and the presence of the steel making plant. The trend in emissions of micro-particles was found quite characteristic of similar semi-urban areas. Originality/value: – The paper demonstrates that a steel making plant adopting best available techniques could have a local impact compatible with the surrounding environment.